AFRICAN BAOBABS WITH A VERY LARGE NUMBER OF STEMS AND FALSE STEMS: RADIOCARBON INVESTIGATION OF THE BAOBAB OF WARANG - PATRUT, Adrian; GARNAUD, Sébastien; KA, Oumar; PATRUT, Roxana T.; DIAGNE, Tomas; LOWY, Daniel A.; FORIZS, Edit; BODIS, Jenő; von REDEN, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The article presents the AMS (accelerator mass spectrometry) radiocarbon dating results of the baobab of Warang, Senegal. The investigation of the baobab revealed that it consists of 18 partially fused stems, which represents the largest number of stems reported for an African baobab. Three stems build the ring that closes a false cavity, while 15 stems grow outside the ring. Seven wood samples were collected from the false cavity and from the outer part of other stems. The dating results evinced that the stems belong to four different generations, out of which the first generation is around 500 years old. We also documented the presence of false stems, which emerge from a large adjacent stem, are triangular in horizontal section and act as an anchor. The baobab of Warang possesses 12 ordinary stems and 6 false stems.